Pengembangan Media Automatic Genetics Propeller Berbasis STEM (Science, Technology, Engineering And Mathematics) Untuk Meningkatkan Literasi Sains Dan Sikap Ilmiah Siswa - Majid, Abdul; Arip, Asep Ginanjar; Nur, Sofyan Hassanudin (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2021)
The purpose of this study is to analyze media applications Automatic Genetics Propeller STEM based To be able to enhance the science literacy and the scientific attitude of students SMA Islam Al-Azhar 5 Cirebon. Approach to composing this thesis using an approach R&D (Research and Development), The data that is needed in this research is employee and theoretical data. Where as engineering for data collection using a test, angkets, observation, and documentation. The population in this research is all of the students XII SMA Islam Al-Azhar 5 Cirebon in school year 2018/2019 a total of 120 students with a data sample of 57 students. Composed of 27 control students and 30 experimental classes.It's based on various tests taken hence the use of media Automatic Genetics Propeeller can enhance student science literacy by 48.6%. In addition to learning Automatic Genetics Propeller media can also significantly enhance a student's scientific attitude and student responses 75,4 % indicate a strong category, that students are happy and helped with it Automatic Genetics Propeller as learning media.